THE ROLE OF PROFITABILITY AND CAPITAL STRUCTURE IN STOCK PRICE FORMATION: AN EMPIRICAL STUDY OF CIGARETTE SUBSECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE DURING 2019-2023 - Anggan Dini Wanodya Gute Ulayya; Kaca Dian Meila; Putri Gantine Lestari (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
The tobacco industry is one of the sectors that contributes significantly to state revenue through taxes and excise, thereby holding a strategic position in the national economy. However, during the period 2019-2023, the stock prices of tobacco subsector companies listed on the Indonesia Stock Exchange showed a declining trend despite the continuous increase in excise revenue. This condition indicates a discrepancy between industry performance and stock price movements, highlighting the importance of examining fundamental company factors, particularly profitability and capital structure, in influencing stock prices. This study aims to analyze the effect of profitability and capital structure on stock prices of manufacturing companies in the tobacco subsector listed on the Indonesia Stock Exchange for the period 2019-2023. The research employs a quantitative approach using panel data regression analysis. The sample was determined using a saturated sampling technique, consisting of four companies that were consistently listed during the observation period. The data used are secondary data obtained from annual financial reports and official publications of the Indonesia Stock Exchange. The results indicate that profitability, proxied by Net Profit Margin (NPM), and capital structure, proxied by Debt to Equity Ratio (DER), have positive and significant effects on stock prices. Simultaneously, both variables significantly influence stock prices. The coefficient of determination (R²) of 0.890 shows that 89% of stock price variation can be explained by profitability and capital structure, confirming their important role in stock price formation.